Marketing research - Aaker, David A.; Kumar, V.; Day, George S. (New York : John Wiley and Sons, 2001)
This book is about: The nature and scope of marketing research; Data collection; Data analysis; Special topics in data analysis; Applications;...
Keywords: Marketing; Marketing research